88 lines
2.2 KiB
TeX
88 lines
2.2 KiB
TeX
% Created 2023-09-29 Fri 10:00
|
|
% Intended LaTeX compiler: pdflatex
|
|
\documentclass[11pt]{article}
|
|
\usepackage[utf8]{inputenc}
|
|
\usepackage[T1]{fontenc}
|
|
\usepackage{graphicx}
|
|
\usepackage{longtable}
|
|
\usepackage{wrapfig}
|
|
\usepackage{rotating}
|
|
\usepackage[normalem]{ulem}
|
|
\usepackage{amsmath}
|
|
\usepackage{amssymb}
|
|
\usepackage{capt-of}
|
|
\usepackage{hyperref}
|
|
\author{Elizabeth Hunt}
|
|
\date{\today}
|
|
\title{}
|
|
\hypersetup{
|
|
pdfauthor={Elizabeth Hunt},
|
|
pdftitle={},
|
|
pdfkeywords={},
|
|
pdfsubject={},
|
|
pdfcreator={Emacs 28.2 (Org mode 9.7-pre)},
|
|
pdflang={English}}
|
|
\begin{document}
|
|
|
|
\tableofcontents
|
|
|
|
\section{Taylor Series Approx.}
|
|
\label{sec:orgcc72ed1}
|
|
Suppose f has \(\infty\) many derivatives near a point a. Then the taylor series is given by
|
|
|
|
\(f(x) = \Sigma_{n=0}^{\infty} \frac{f^{(n)}(a)}{n!}(x-a)^n\)
|
|
|
|
For increment notation we can write
|
|
|
|
\(f(a + h) = f(a) + f'(a)(a+h - a) + \dots\)
|
|
|
|
\(= \Sigma_{n=0}^{\infty} \frac{f^{(n)}(a)}{h!} (h^n)\)
|
|
|
|
Consider the approximation
|
|
|
|
\(e = |f'(a) - \frac{f(a + h) - f(a)}{h}| = |f'(a) - \frac{1}{h}(f(a + h) - f(a))|\)
|
|
|
|
Substituting\ldots{}
|
|
|
|
\(= |f'(a) - \frac{1}{h}((f(a) + f'(a) h + \frac{f''(a)}{2} h^2 + \cdots) - f(a))|\)
|
|
|
|
\(f(a) - f(a) = 0\)\ldots{} and \(distribute the h\)
|
|
|
|
\(= |-1/2 f''(a) h + \frac{1}{6}f'''(a)h^2 \cdots|\)
|
|
|
|
\subsection{With Remainder}
|
|
\label{sec:org7dfd6c7}
|
|
We can determine for some u \(f(a + h) = f(a) + f'(a)h + \frac{1}{2}f''(u)h^2\)
|
|
|
|
and so the error is \(e = |f'(a) - \frac{f(a + h) - f(a)}{h}| = |\frac{h}{2}f''(u)|\)
|
|
|
|
\begin{itemize}
|
|
\item\relax [\url{https://openstax.org/books/calculus-volume-2/pages/6-3-taylor-and-maclaurin-series}]
|
|
\begin{itemize}
|
|
\item > Taylor's Theorem w/ Remainder
|
|
\end{itemize}
|
|
\end{itemize}
|
|
|
|
|
|
\subsection{Of Deriviatives}
|
|
\label{sec:org1ec7c9b}
|
|
|
|
Again, \(f'(a) \approx \frac{f(a+h) - f(a)}{h}\),
|
|
|
|
\(e = |\frac{1}{2} f''(a) + \frac{1}{3!}h^2 f'''(a) + \cdots\)
|
|
|
|
\(R_2 = \frac{h}{2} f''(u)\)
|
|
|
|
\(|\frac{h}{2} f''(u)| \leq M h^1\)
|
|
|
|
\(M = \frac{1}{2}|f'(u)|\)
|
|
|
|
\subsubsection{Another approximation}
|
|
\label{sec:org16193b9}
|
|
|
|
\(\text{err} = |f'(a) - \frac{f(a) - f(a - h)}{h}|\)
|
|
|
|
\(= f'(a) - \frac{1}{h}(f(a) - (f(a) + f'(a)(a - (a - h)) + \frac{1}{2}f''(a)(a-(a-h))^2 + \cdots))\)
|
|
|
|
\(= |f'(a) - \frac{1}{h}(f'(a) + \frac{1}{2}f''(a)h)|\)
|
|
\end{document} |